A Case Series and Literature Review of Vertebral Artery Stump Syndrome - Zhang, Wenbin; Wang, Shouchun; Li, Chao; Wang, Zhongxiu; Yue, Feixue; Zhou, Jie; Song, Kangjia; Wang, Chao; Wang, Yujiao; Shi, Mingchao (Frontiers in Neurology, 2022)
Purpose Stump syndrome refers to cerebral ischaemic symptoms caused by an embolus from a previously occluded ipsilateral artery that occludes a down-stream artery. It can be divided into two types: carotid stump syndrome and vertebral artery stump syndrome (VASS). At present, there is limited clinical experience with VASS. We aimed to propose a more precise diagnostic standard for VASS, and to share our experience with handling this condition. Materials and Methods We retrospectively collected data of patients who were treated with endovascular thrombectomy in the stroke centre of the First Hospital of Jilin University from January 2016 to March 2020. After screening patients with posterior-circulation acute ischaemic stroke, we selected patients who had an acute occlusion of an intracranial artery in the context of a previously occluded ipsilateral vertebral artery origin, as confirmed by digital subtraction angiography. Results Eleven patients met our inclusion criteria. Nine patients achieved recanalization of both extracranial and intracranial occluded arteries, one patient had modified thrombolysis in cerebral infarction grade 3, and eight patients had grade 2b. Residual stenosis of recanalized intracranial arteries was less than 30% in all cases, while three patients had embolism of distal arteries. No dissection or subarachnoid haemorrhage occurred. Two patients didn't reach vascular recanalization. Among the nine patients with recanalized artery, four had a 90-day modified Rankin Scale score ≤ 3 (favourable outcome), and four patients died; As for the two non-recanalized patients, one had a mRS score of 5 and one died. Conclusion VASS is a clinical syndrome caused by embolic occlusion of a distal intracranial artery occluded ipsilateral extracranial vertebral artery. Antegrade blood flow from the collateral vessels, distal embolic occlusion and mild or no residual stenosis of the occluded intracranial artery after recanalization are notable features of this clinical event. Endovascular thrombectomy may be effective for treating VASS.